P011 ADHERENT-INVASIVE ESCHERICHIA COLI UTILIZES SERINE CATABOLISM TO OUTCOMPETE ITS COMMENSAL COMPETITORS. (18th January 2018) - Kitamoto, Sho; Kitamoto, Hiroko; Kamada, Nobuhiko
Abstract: Background: Crohn's disease (CD) patients are often colonized by adherent-invasive Escherichia coli (AIEC). Although the colonization by AIEC is known to contribute to the pathogenesis of CD, the mechanisms by which AIEC thrives within the inflamed intestine in CD patients remain elusive. Methods: To elucidate the mechanisms by which AIEC outcompetes commensal non-pathogenic E. coli (cEC) in the intestine, in vivo competition of AIEC (strain LF82) and cEC (strain MG1655) was performed using co-colonization of the two strains in germ-free mice. Dextran sodium sulfate (DSS) was given to the co-colonized mice to mimic inflammatory environments. To identify the unique metabolic pathways that are utilized by AIEC during inflammation, transcriptomic changes in E. coli strains in the inflamed gut were analyzed by RNAseq. Amino acid (AA) defined diets were applied to bacterial in vivo competition to assess the impact of dietary serine on AIEC bloom. Results: AIEC gained the growth advantage over cEC during DSS colitis. Intestinal inflammation reprogramed bacterial metabolic pathways from carbohydrate metabolism toward amino acid metabolism, particularly serine utilization, in AIEC. An isogenic mutant AIEC strain that lacks serine utilization genes failed to outcompete cEC in the inflamed gut. The deprivation of dietary serine also prevented outgrowth of AIEC in the inflamed but not in the steady-state gut in vivo. Conclusion: AIEC utilizes serine catabolism pathways to gain a growth advantage over cEC in the inflamed gut. Targeting unique metabolic pathways exploited by AIEC may selectively eliminate the pathogenic strains of gut bacteria without influencing beneficial commensal microbiota.